Analisis Pengaruh Karakteristik Pekerjaan dan Karakteristik Individu Terhadap Kinerja Pegawai Melalui Motivasi Kerja (Studi Kasus Pegawai Sekretariat DPRK Kabupaten Pidie Jaya) - Ali, Muhammad; Yusuf, M.; Harahap, Imam Taufik (Singkite Journal, 2025)
The research is a case study of 60 employees of the Pidie Jaya DPRK Secretariat using an associative method with a quantitative approach. And the analysis answers the hypothesis using a path analysis model. The research results show that, 1) There is a direct and indirect influence of job characteristics on employee performance of 27.13%. 2) There is a direct and indirect influence of individual characteristics on employee performance of 24.73%. 3) Simultaneously, the influence of job characteristics and individual characteristics is significant on employee performance, amounting to 40,6.%. 4) There is an influence of work motivation on employee performance of 61.7%. 5) There is a direct and indirect influence of job characteristics on employee work motivation of 34.22%. 6) There is a direct and indirect influence of individual characteristics on work motivation of 29.30%.